DURING A CRISIS CAUSED BY A PANDEMIC, IT IS BEST TO INVEST IN GREEN ENERGY - Mihajlović, Marija; Stošić Mihajlović, Ljiljana; Trajković, Svetlana (Journal of process management and new technologies, 2021)
Numerous analyzes show that various factors, including mass vaccination and better virus control, have helped to change policy of job restraint and closure, especially in the SME sector. The governments of almost all countries have recognized that geographically targeted and sector-specific measures are more acceptable to the people and thus reduce the negative economic consequences of a pandemic. However, the fact is that the health risks are still very pronounced, so it is necessary to establish a balance between public health measures against the virus and measures to support workers and companies affected by the consequences of the pandemic. The question is: where to invest during the pandemic, and especially after, when the pandemic passes? In this paper, we will talk about the measures of the state to help the economy, now that it is the most difficult. In particular, we will talk about sectors that have a future, and are related to the energy sector (especially RES), economy and environment